Implementing the Triple Helix model in a non-Western context: an institutional logics perspective - Yuzhuo Cai (Triple Helix, 2014)
While there is a common belief among policymakers and academics around the world that Triple Helix relationships between university, industry and government provide optimal conditions for innovation, it should be noted that the Triple Helix concept has been developed from the experience of advanced economies in the West. There is a lack of theoretical considerations and empirical evidence on whether the Triple Helix model is applicable in non-Western contexts. Following the understanding that the evolution of an ideal Triple Helix model is facilitated by certain institutional logics in Western societies, this paper takes China as an example to examine how the institutional logics in China are different from those of the West and how the institutional logics in China would promote or impede the development of the Triple Helix model in China in light of an extensive review of the relevant literature and policy documents. The study suggests that to optimise the Chinese innovation policies, China needs on the one hand to adjust some elements of its institutional environment to facilitate the interactions between key innovation actors and on the other hand to be innovative in developing its own Triple Helix modes given the unique Chinese institutional environment which will persist in the foreseeable future.
Keywords: 330; Triple Helix; Innovation system; Institutional logics; China; Institutionalism